An Anode-Free Zn–Graphite Battery - Wang, Gang; Zhu, Minshen; Chen, Guangbo; Qu, Zhe; Kohn, Benjamin; Scheler, Ulrich; Chu, Xingyuan; Fu, Yubin; Schmidt, Oliver G.; Feng, Xinliang (Advanced Materials, 2022)
The anode-free battery concept is proposed to pursue the aspiration of energy-dense, rechargeable metal batteries, but this has not been achieved with dual-ion batteries. Herein, the first anode-free Zn–graphite battery enabled by efficient Zn plating–stripping onto a silver-coated Cu substrate is demonstrated. The silver coating guides uniform Zn deposition without dendrite formation or side reaction over a wide range of electrolyte concentrations, enabling the construction of anode-free Zn cells. In addition, the graphite cathode operates efficiently under reversible bis(trifluoromethanesulfonyl)imide anion (TFSI−) intercalation without anodic corrosion. An extra high-potential TFSI− intercalation plateau is recognized at 2.75 V, contributing to the high capacity of graphite cathode. Thanks to efficient Zn plating–stripping and TFSI− intercalation–deintercalation, an anode-free Zn–graphite dual-ion battery that exhibits impressive cycling stability with 82% capacity retention after 1000 cycles is constructed. At the same time, a specific energy of 79 Wh kg−1 based on the mass of cathode and electrolyte is achieved, which is over two times higher than conventional Zn–graphite batteries (<30 Wh kg−1).
CRIS-Team Scopus Importer:2023-03-20
Keywords: anion intercalation; anode-free batteries; dual-ion batteries; plating–stripping; Zn batteries